Interactions between aerosol organic components and liquid water content during haze episodes in Beijing - X. Li; S. Song; W. Zhou; J. Hao; D. R. Worsnop; D. R. Worsnop; J. Jiang (Atmospheric Chemistry and Physics, 2019)
Aerosol liquid water (ALW) is ubiquitous in ambient aerosol and plays an important role in the formation of both aerosol organics and inorganics. To investigate the interactions between ALW and aerosol organics during haze formation and evolution, ALW was modelled based on long-term measurement of submicron aerosol composition in different seasons in Beijing. ALW contributed by aerosol inorganics (ALWinorg) was modelled by ISORROPIA II, and ALW contributed by organics (ALWorg) was estimated with κ-Köhler theory, where the real-time hygroscopicity parameter of the organics (κorg) was calculated from the real-time organic oxygen-to-carbon ratio (O∕C). Overall particle hygroscopicity (κtotal) was computed by weighting component hygroscopicity parameters based on their volume fractions in the mixture. We found that ALWorg, which is often neglected in traditional ALW modelling, contributes a significant fraction (18 %–32 %) to the total ALW in Beijing. The ALWorg fraction is largest on the cleanest days when both the organic fraction and κorg are relatively high. The large variation in O∕C, from 0.2 to 1.3, indicates the wide variety of organic components. This emphasizes the necessity of using real-time κorg, instead of fixed κorg, to calculate ALWorg in Beijing. The significant variation in κorg (calculated from O∕C), together with highly variable organic or inorganic volume fractions, leads to a wide range of κtotal (between 0.20 and 0.45), which has a great impact on water uptake. The variation in organic O∕C, or derived κorg, was found to be influenced by temperature (T), ALW, and aerosol mass concentrations, among which T and ALW both have promoting effects on O∕C. During high-ALW haze episodes, although the organic fraction decreases rapidly, O∕C and derived κorg increase with the increase in ALW, suggesting the formation of more soluble organics via heterogeneous uptake or aqueous processes. A positive feedback loop is thus formed: during high-ALW episodes, increasing κorg, together with decreasing particle organic fraction (or increasing particle inorganic fraction), increases κtotal, and thus further promotes the ability of particles to uptake water.